Influence of iVO2max determination on time spent at VO2max during continuous cycling to exhaustion - Merry, K. L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The minimal exercise intensity that elicits VO2max during a maximal incremental test (iVO2max) may allow the longest time spent at a high VO2 (. 95% VO2max) during continuous exercise to exhaustion (Billat et al., 1999). The purpose of this study was to compare the time to exhaustion (TTE) and time spent at a high level of oxygen uptake (VO2) during two continuous cycle ergometer exercises to exhaustion at iV2max Methods: Nine male triathletes (age 31.6 ± 10.2 years, body mass 73.3 ± 6.1 kg, height 1.79 ± 0.07 m, VO2max 3.52 ± 0.49 L/min) attended the laboratory on four separate occasions over a period of 4 weeks. During trials 1 and 2, in a random order, participants performed two maximal incremental cycle ergometer tests with different stage durations (1 min and 3 min) for the determination of iVO2max(1 min) and iVO2max(3 min). During visits 3 and 4, participants performed two continuous cycles to exhaustion at iVO2max(1 min) (CONT1) and iVO2max(3 min) (CONT3) also in a random order. Results: iVO2max(1 min) was significantly greater (P < 0.05) than iVO2max(3 min) (337 ± 36 W vs. 292 ± 43 W) (P < 0.05). There was no significant difference (P > 0.05) between iVO2max(1 min) and iVO2max(3 min) for VO2max (3.59 ± 0.48 L/min vs. 3.52 ± 0.51 L/min). The mean TTE measured during CONT3 was significantly longer (P < 0.05) than CONT1 (511.7 ± 189.2 s vs. 224.9 ± 54.2 s). The mean time spent at VO2max (T@VO2max) was significantly longer (P < 0.05) during CONT3 than CONT1 (199.3 ± 220.0 s vs. 11.6 ± 26.8 s), and the mean time spent above 95% VO2max (T@95%VO2max) was significantly longer (P < 0.05) during CONT3 than CONT1 (306.4 ± 238.0 s vs. 64.3 ± 61.2 s). Discussion: In conclusion, these results show that when exercising continuously to exhaustion at iVO2max time spent at a high level of VO2 is significantly longer when iVO2max(3 min) is used to determine iVO2max